(untitled) (Research, Society and Development, 2022)
To analyze the use and causes of early removal of the peripherally inserted central catheter in newborns and to develop strategies in the future for better use and maintenance of these catheters, providing more quality care for newborns admitted to the Neonatal Intensive Care Unit of a hospital university in southern Brazil. A cross-sectional retrospective quantitative study carried out through the review of peripherally inserted central catheter follow-up forms, from June 2014 to December 2018. A total of 216 newborns used peripherally inserted central catheter, 84% of which were premature. The main reasons for withdrawal were due to the end of treatment (37%), followed by obstruction (22%), breakage (17%), phlebitis (11%), extrusion (9%) and death (4%), respectively. In 63% of the newborns, it was found that the removal occurred early, with 8 days (interquartile range: 5; 12) after catheter insertion. Difficulties in maintaining the catheter were also found in 56% of cases. It was verified that the early exit of the catheter occurred more frequently when 4 antibiotics were used or more 76.3% (p<0.001) and when other drugs were used 66.3% (p = 0.038). It is concluded from the present study that the peripherally inserted central catheter is an important resource in prolonged intravenous therapy in the care of newborns and that early removal happens with high frequency, with the identification of some factors that should be avoided. This type of catheter must be monitored by professionals duly trained both for its insertion and for its maintenance.